SUSYQM in nuclear structure: Bohr Hamiltonian with mass depending on the deformation - Bonatsos, D.; Georgoudis, P. E.; Lenis, D.; Minkov, N.; Quesne, C. (HNPS Advances in Nuclear Physics, 2019)
A well known problem of the Bohr Hamiltonian for the description of nuclear collective motion is that the nuclear moment of inertia increases with deformation too fast. We show that this can be avoided by allowing the nuclear mass to depend on the deformation. The resulting Hamiltonian is solved exactly, using techniques of Supersymmetric Quantum Mechanics